An EFL Teacher's Investment in Digital Multimodal Composing. (8th July 2020) - Jiang, Lianjiang; Yu, Shulin; Zhao, Yi
Abstract: Although there is a growing call for L2 teachers to invest in using digital multimodal composing (DMC) as an instructional activity, there is a paucity of research on whether and how L2 teachers invest in DMC, and the impact of DMC on their teaching and changing identities remains underexplored. This study reports on a longitudinal case study of an EFL teacher's investment in DMC in a university-based EFL classroom in China. A qualitative analysis of the data gathered from observation, interview, and informal conversation reveals that through investing in DMC this teacher started to renegotiate herself as a composing guide, a peer mentor, and a change agent. These shifts of identity were mainly driven by her enhanced cultural and social capital after investing in DMC, despite constraints from ideology and the policing of technology, language-dominant assessment, and other institutional demands. Implications on using DMC are also discussed.